ʺEnhancing the expertise of teaching staff on the basis of general secondary education institutions through 30-hour modules as an outcome of the diversification of education servicesʺ - Luniachek, V.; Ruban, N. (Problems of Engineer-Pedagogical Education, 2022)
The paper considers the issue of professional development of teachers and heads of general secondary education institutions through 30-hour modules in the context of the global Coronavirus pandemic. Specific emphasis is placed on the diversification of forms and methods of professional development in accordance with the provisions of the Law of Ukraine "On Education" (2017) and other regulations. Particular attention is drawn to the specifics of these procedures in the pandemic. The authors also prove the need for annual 30- hour training modules for teachers on the basis of general secondary education institutions, which can solve a number of logistical issues, taken the mobility limitations of subjects and objects of this process in the pandemic. The presented materials also contain 30-hour modules developed by the authors that can be offered to consumers of education services for advanced training and substantiate the relevance of the proposed topics. These modules deal with the questions of scientific-methodological and technological basics of designing the internal system of quality assurance of education in general secondary education institutions, basics of forming a strategic plan of general secondary education institutions, global trends in education, products of teachers’ innovative work as intellectual property, academic integrity, cloud technologies in teaching and management of education institutions, etc. The paper specifically substantiates the expediency of conducting 30-hour modules devoted to implementing creative learning technologies into the educational process, which is an urgent need of the time. An important component of the work is the position of the authors on the study of labour costs of teachers and research staff in distance learning and training caused by the global Coronavirus pandemic and the need for sound management decisions to adequately compensate teachers and research staff for their time and personal resources that they spend in the process of the above activities, which is believed to significantly influence their morale and health.